Magnetic Resonance Imaging in Situ Visualization of an Electrochemical Reaction under Forced Hydrodynamic Conditions - Serial, María Raquel (2018)
Magnetic resonance imaging (MRI) has proven to be a powerful tool for the characterization and investigation of in situ chemical reactions. This is more relevant when dealing with complex systems, where the spatial distribution of the species, partition equilibrium, flow patterns, among other factors have a determining effect over mass transport and therefore over the reaction rate. The advantage of MRI is that it provides spatial information in a noninvasive way and does not require any molecular sensor or sample extraction. In this work, MRI is used to fully characterize an electrochemical reaction under forced hydrodynamic conditions. Reaction rates, flow patterns, and quantitative concentration of the chemical species involved are spatially monitored in situ in a complex system that involves metallic pieces and a heterogeneous cementation reaction. Experimental data are compared with numerical simulations.